A guideline for development a short-term classical guitar curriculum in Thailand - Natthawat Khositditsayanan; Chaloemchai Sosutha; Kanit Promnil (Gemilang Maju Publikasi Ilmiah (GMPI), 2021)
The objectives of this research were to (1) study criteria for practice of the classical guitar test to be used as a guideline for the entrance examination for higher education in Thailand and (2) find the ways to develop curriculum of a short- term classical guitar for entrance examinations of higher education by studying the information from documents, principles, theories, and criteria of the classical guitar test to be used as a guideline for admission to higher education in Thailand. The results of the research were as follows 1) criteria for practice of classical guitar test to be used as a guideline for the entrance examination for higher education. There were 2 parts of the contents for examination including technically, candidates must be able to practice the scale, length was not more than 4 sharps, 4 flats in major and minor scales with arpeggio and the piece contained and exercise song and 2 general pieces, difficulty from Intermediate to advanced and there were differences in style of music eras or musical styles from different composers and all the pieces that test takers must play from memory, and 2) curriculum of a short-term classical guitar for tertiary entrance examinations that had a content consists of 2 parts. The first one, the content and course details, were the curriculum competency, course descriptions, tools, materials, equipment, training materials and learning resources and background knowledge and qualifications of trainees and the second one, measurement and evaluation consisted of 3 parts : a post-test to review the process and the duration of attending the training was not less than 80 percentage of the training time according to the curriculum.